A Neutrosophic Approach for Opponent Analysis and Game Strategy Formulation in College Volleyball - Bogang Huang (Neutrosophic Sets and Systems, 2025)
In competitive college volleyball, effective opponent analysis is crucial for strategic decisionmaking, particularly when facing teams with varying performance dynamics. This study introduces a QNeutrosophic Soft Set (QNSS) approach to opponent analysis, enabling multi-context decision evaluation based on a granular assessment of opponent characteristics across different game conditions. Our QNSS proposes a novel Context-wise Aggregation Operator (CWA) that captures the nuanced relationships between contexts and parameters in QNSS, providing a flexible aggregation mechanism that not only accounts for the varying importance of different contexts but also emphasizes the multiplicative relationships between membership values. Our framework presents neutrosophic best-worst method to compute criteria weights by ensuring more diverse and well-distributed criteria values and introduces a regularization-based spread maximization function to prevent weight convergence and ensure proper consistency handling through a nonlinear optimization model. Then, a customized fuzzy ARAS is computed to assess and rank the different playing strategies. Further, we introduce a real case study on European volleyball championship for senior men's national teams in Europe, in which decision-makers. Proof of concept analysis is conducted on real case studies validated to the advantages of the proposed approach, and compared the methods against state-of-the-art studies, implying insightful boosting to the opponent analysis and game planning. DOI: 10.5281/zenodo.15069506